Projecting meat and cereals demand for China based on a meta-analysis of income elasticities - De Zhou; Xiaohua Yu; David Abler; Danhong Chen (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
There are many projections for China's food demand, and the projection results differ significantly from each other. Different values for income elasticities could be a major reason. This study projects meat and cereals demand for China based on a meta-analysis of the income elasticity estimates using a collection of 143 and 240 income elasticity estimates for cereals and meat products, respectively, from 36 primary studies. We find that income elasticities for most cereals (general cereals, rice, and coarse grains) and all meat products (general meat, pork, poultry, beef & mutton) tend to decline as per capita income increases, except for wheat, which increases. Taking this into account, differences between consumption projections based on time-varying income elasticities and values based on constant elasticities are substantial in quantities and increase over time.
Keywords: D12; Q11; 330; projections; food demand; income elasticity; China; meta-analysis